IGF-I Gene Therapy in Aging Rats Modulates Hippocampal Genes Relevant to Memory Function - Pardo, Joaquin (2017)
In rats, learning and memory performance decline during normal aging, which makes this rodent species a suitable model to evaluate therapeutic strategies. In aging rats, insulin-like growth factor-I (IGF-I), is known to significantly improve spatial memory accuracy as compared to control counterparts. A constellation of gene expression changes underlie the hippocampal phenotype of aging but no studies on the effects of IGF-I on the hippocampal transcriptome of old rodents have been documented. Here, we assessed the effects of IGF-I gene therapy on spatial memory performance in old female rats and compared them with changes in the hippocampal transcriptome. In the Barnes maze test, experimental rats showed a significantly higher exploratory frequency of the goal hole than controls. Hippocampal RNA-sequencing showed that 219 genes are differentially expressed in 28 months old rats intracerebroventricularly injected with an adenovector expressing rat IGF-I as compared with placebo adenovector-injected counterparts. From the differentially expressed genes, 81 were down and 138 upregulated. From those genes, a list of functionally relevant genes, concerning hippocampal IGF-I expression, synaptic plasticity as well as neuronal function was identified. Our results provide an initial glimpse at the molecular mechanisms underlying the neuroprotective actions of IGF-I in the aging brain.